Migrationsliteraturen in Europa - Binder, Eva; Mertz-Baumgartner, Birgit (innsbruck university press, 2012)
Looking at literary texts, the volume opens up innovative and differentiated perspectives on the socio-politically controversial phenomenon of migration. It draws on Hartmut Böhme's notion of literature as a discursive system of actions and symbols that contributes to the self-reflection of societies, even though - or rather precisely because - the 'disturbing' character of literature is tolerated and controlled to a certain extent. The analyses gathered in this volume look at contemporary European literature and focus on the question of how experiences of migration are thematized and aesthetically shaped in literary texts. In doing so, concepts of migrant identity, transcultural topographies of memory, phenomena of drawing and transgressing boundaries/borders, as well as notions of in-between spaces come into focus. Particular attention is paid to questions regarding the possibility of a "poetics of migration" by examining textual phenomena such as polyperspectivity, forms of multilingualism, and techniques of pseudo-translation through the lens of transcultural narratology.